Case Report: CD8+ T-Lymphocyte Deficit: A Prerequisite for Pasteurella spp. Infection? - Denes, Eric; Fiorenza, Fabrice; Armendariz, Mateo; Martin, Christian (Frontiers in Medicine, 2021)
Background: Immunity against Pasteurella spp. is not well known for humans. Methods: We’ve tested T CD8+ lymphocytes in a patient with a chronic prosthetic joint infection due to Pasteurella spp. to search for a deficit which could have favored her infection. As this deficit was found, we’ve searched for such a deficit in other patients with Pasteurella spp. Infections, either acute or subacute. Results: Eight patients were tested and all had a persistent T CD8+ lymphocytes deficit. This is striking as these cells are involved in the response to this type of infection in animal models. Conclusion: The authors suggest that a deficit in CD8+ T lymphocytes can be one of the causes for the onset of infections with P. multocida.